KOMUNIKASI DAN PENGELOLAAN EMOSI PADA SISWA SMA DARUSSALAM BLOKAGUNG BANYUWANGI - Agus Baihaqi; Zami Mabekruroh (Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This study aims to determine the role of communication when emotions experienced by humans, one of that experienced are happening during high school. It has an attraction for further research because adolescence is the initial period of emotional management. But for managing emotions, not all students can manage their feelings. For this reason, this study aims to determine how capable students are in controlling their emotions. In this research, the type of research used is descriptive qualitative. Data collection techniques use observation, interviews, and documentation to understand the phenomena experienced by research subjects, such as behavior, actions, and others in a natural context. This study uses descriptive research, descriptive research is research that describes a situation or event. The results of this study indicate how capable students are in managing their emotions, the causes of emotions, factors that influence emotional management, and factors that cause emotions, also the role of communication in managing emotions in Darussalam high school students, Blokagung, Banyuwangi Regency.